The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/macp.201600070
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Carrier Transport and Trapping in Photorefractive Polymer Composites Using Photoemission Yield Spectroscopy in Air

Abstract: Carrier trapping in organic photorefractive (PR) composites is affected by the bulk state (which can be varied by modifying the molecule structure and processing method used) and the presence of dipolar molecules. Such situations complicate the understanding of carrier trapping in PR composites. The density of states (DOS) provides direct information about carrier trapping in materials. Here, the first attempt to directly measure the DOS in PR composites is performed to investigate the effect of the change of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Organic photorefractive (PR) polymers have wide potential for updatable holographic imaging and dynamic holographic displays. Dynamic holography is the ultimate in three-dimensional (3D) imaging and is expected to be key technology for a next-generation display system. Photorefractive phenomena are based on refractive index modulation derived from the distributed space-charge field through the Pockels (first-order optical nonlinearity) effect. Since the first study of organic photorefractive polymers was reported, numerous research investigations have focused on PR polymers. , …”
Section: Introductionmentioning
confidence: 99%
“…Organic photorefractive (PR) polymers have wide potential for updatable holographic imaging and dynamic holographic displays. Dynamic holography is the ultimate in three-dimensional (3D) imaging and is expected to be key technology for a next-generation display system. Photorefractive phenomena are based on refractive index modulation derived from the distributed space-charge field through the Pockels (first-order optical nonlinearity) effect. Since the first study of organic photorefractive polymers was reported, numerous research investigations have focused on PR polymers. , …”
Section: Introductionmentioning
confidence: 99%
“…Among various organic PR materials, gust-host systems, prepared by doping small molecular NLO chromophores into polymeric photoconductors, are the most studied for practical application because of their eases of fabrication. [7,8] However, with the increasing of NLO chromophore doping concentration, the unfavorable antiparallel packing of chromophores resulting from the strong interchromophore dipole-dipole interactions gradually appeared, leading to a decreased PR effect. [9] Recently, some nonlinear molecules such as hyper-structured molecules (HSMs), [10] star-shaped molecules, [11] dendritic molecules, [12] etc.…”
Section: Introductionmentioning
confidence: 99%